Comparing Efficacy Of Itraconazole Versus Itraconazole Plus 2% Ketoconazole Shampoo In The Treatment Of Pityriasis Versicolor: Retrospective Study (Annals of Medical Research, 2021)
None
Keywords: Tinea Versicolor, İtraconazole, Ketoconazole Shampoo